Agile Organization Implementation Evaluation to Improve Effectiveness and Efficiency: The Case of Pol PP Unit at Muara Enim Regency - Juniarty, Tien; Basyith, Abdul; Yulanda, Delvina (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The Civil Service Police Unit (Satpol PP) of Muara Enim Regency faces complex challenges, including limited resources, rigid bureaucracy, and increasing public demands for high-quality services. In response to these dynamics, Satpol PP has begun to implement Agile principles as a strategic approach to enhance work effectiveness and efficiency. This approach emphasizes cross-functional collaboration, task flexibility, digital technology utilization, and fast, adaptive decision-making. Initial results of Agile implementation show significant positive impacts, including an increase in community compliance from 64% to 91%, a reduction in violations from 867 cases in 2020 to 173 cases in 2024, and an 80% rise in personnel productivity. Moreover, public report responses have become faster, and budget utilization has become more efficient. However, the Agile approach still encounters several obstacles, including resistance to change, limited leadership support, and regulatory frameworks that are not yet fully adaptable to this new method. Therefore, a comprehensive evaluation of Agile implementation in the governmental context is crucial to ensure the sustainability and success of organizational transformation within Satpol PP Muara Enim Regency